1981
DOI: 10.1002/1097-0142(19810315)47:6+<1505::aid-cncr2820471411>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and biochemical characteristics of isolated and cultured pancreatic ducts

Abstract: Rat and hamster pancreatic ducts were isolated by digestion with collagenase plus chymotrypsin and were cultured for eight weeks in an agarose matrix. Freshly isolated and cultured ducts were characterized morphologically and biochemically. The in vivo morphology of the ducts was maintained in vitro, although certain differences were noted. Both interlobular and intralobular ducts could be identified. gamma-Glutamyltranspeptidase and Mg-ATPase were stable enzymatic activities of the ducts of both species; alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Since a specific ductal cell marker has yet to be described, morphological and biochemical criteria shown previously to be indicative of ductal cells (7,10,15) were used to characterize the MIA PaCa-2 cell line.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Since a specific ductal cell marker has yet to be described, morphological and biochemical criteria shown previously to be indicative of ductal cells (7,10,15) were used to characterize the MIA PaCa-2 cell line.…”
supporting
confidence: 93%
“…The predominant cell type comprising the rat (6) and human (7) pancreatic ductal systems are structurally similar throughout the different classes of ducts. Isolation and culture of rat (8)(9)(10) and human pancreatic ducts (Sarras et al, in preparation) have been used previously as a model to study ductal function. Using isolated pancreatic ducts of the pancreatic ductal system have confirmed these findings and have demonstrated that principal cell secretions contain highly sulfated mucins.…”
mentioning
confidence: 99%
“…It should be mentioned, however, that as compared with PANC-I cells, significantly higher specific activities were found in both cultured rat and human ducts. This is in agreement with previous studies by Githens et al (29) that indicate that unlike all other enzyme systems monitored, y-glutamyltranspeptidase activity increases with time during culture of rat pancreatic ducts. In contrast, we observed significantly higher specific activities of this enzyme in rat acini, MDCK cells, and L cells.…”
Section: Discussionmentioning
confidence: 89%
“…In comparison with the in situ morphology of the epithelium of rat (M. E. Madden and M. P. Sarras, Jr., in preparation) and human(9) pancreatic ducts, PANC-1 cells grown on a permeable support appear similar to the epithelium observed in the smaller interlobular ducts. As would be expected for an epithelial cell, PANC-1 cells contain cytokeratin, an epithelial class of intermediate filaments.Based on a previous study by Githens et al(29)…”
mentioning
confidence: 90%
“…This modified digestive procedure both simplified the process and increased the cell yield. In the 1980s, Githens et al (1981Githens et al ( , 1987 and Githens and Whelan (1983) established the explant culture system, which was known as 'classical culture system' and was widely accepted during that period. Nevertheless, explant cultivation takes several weeks, although it is still the most cost-effective method.…”
Section: Discussionmentioning
confidence: 99%